STATISTICAL ANALYSIS OF WIND SPEED DISTRIBUTION BASED ON WEIBULL AND RAYLEIGH METHODS OF ISKENDERUN-TURKEY - Akpınar, Ebru; Akpınar, Sinan; Balpetek, Nilay (My University, 2018)
In this study, the statistical analysis of wind power density and wind speeddistribution parameters in İskenderun was investigated using the hourly windspeed data measured by the General Directorate of Meteorology between2005 and 2014. Weibull and Rayleigh distributions were used for modelingand the success of this modeling process was evaluated according to theparameters of $R^2$, RMSE and $x^2$. The result of the study showed thatIskenderun has a mean wind speed of 2.82 m/s with a maximum value of 4.5m/s in July of 2006 and a minimum value of 1.68 m/s in November of 2012while the corresponding mean wind power density is approximately 19.16W/$m^2$for the whole year. The Weibull distribution function was found to bemore appropriate than the Rayleigh distribution function.
Keywords: Meteoroloji ve Atmosferik Bilimler; İstatistik ve Olasılık